(untitled) (Studia Prawnicze / The Legal Studies, 2013)
W tym opracowaniu autorka skupia się na tym ostatnim rodzaju broni autonomicznej – w zasadzie całkowicie autonomicznej. Na wstępie należy zauważyć, że jak na razie taka broń jeszcze nie istnieje. Jednak prawnicy powinni już teraz przewidywać wpływ takich technologii na międzynarodowe prawo humanitarne oraz sposób prowadzenia konfliktów zbrojnych. Teza tego artykułu jest następująca: użycie broni autonomicznej byłoby niezgodne z podstawowymi zasadami międzynarodowego prawa humanitarnego, takimi jak zasada rozróżniania, proporcjonalności oraz konieczności wojskowej. Broń taka nie jest w stanie sprostać wymogom płynącym z tych zasad. Jako takie jej użycie stanowiłoby zagrożenie dla osób i ludności cywilnej. Są jednak autorzy, którzy uważają, że taki zakaz nie miałby większego sensu oraz że rozwój broni autonomicznej jest nieunikniony i będzie następował stopniowo. Nawet więcej, autonomia systemów broni może pozytywnie wpłynąć na promocję celów praw wojny w niektórych konfi guracjach technologicznych i okolicznościach operacyjnych, lecz w innych nie. Jak postaram się jednak wykazać poniżej, wady zastosowania broni autonomicznej wykluczają jej legalność. W moim przekonaniu legalne jest zastosowanie autonomicznych urządzeń, których celem jest rozpoznanie, identyfi kacja celu, ale nie autonomicznych broni zdolnych atakować cel bez ingerencji czynnika ludzkiego. Along the rapid development and proliferation of autonomous robotic weapons, machines begin to replace people on the battlefields. The use by the USA of Predators or Reapers and other unmanned aerial vehicles (so called drones) in Afghanistan, Pakistan and other places in the world clearly signals distancing of the soldiers from their targets. Some military and robotics experts have predicted that “killer robots” – fully autonomous weapons that could select and engage targets without human intervention – could be developed within 20 to 30 years. At present, military officials generally say that humans will retain some level of supervision over decisions to use lethal force, but their statements often leave open the possibility that robots could one day have the ability to make such choices on their own power. In this paper I will concentrate on the last kind of autonomous weapons, namely fully autonomous ones. It should however be noted that so far such a weapon does not yet exist. Nonetheless, lawyers should already be anticipating the effect of these technologies on international humanitarian law and the conduct of warfare. The thesis of the paper goes as follows: the use of autonomous weapons would be contrary to the basic and fundamental principles of international humanitarian law such as the principle of distinction, proportionality and military necessity and thus illegal. Such weapons are not capable of meeting the conditions enshrined in these principles. As such their use would threaten the well-being, life and health of civilians and civilian populations. On the other hand, there are scholars who are of the opinion that prohibiting the use of autonomous weapons would make no sense at all and that the development of such weapons is inevitable and will take place gradually. Moreover, autonomy in weapon systems might positively promote the aims of the laws of war in some technological configurations and operational circumstances – but not in others. As I will try to demonstrate below, the drawbacks of the use of autonomous weapons are of such magnitude that they exclude its legality. In my opinion, it is legal to use autonomous devices aimed at target identification but not autonomous weapons capable of attacking the target without human interference.